2018
DOI: 10.3389/fimmu.2017.01916
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Typhi Bactericidal Antibodies Reduce Disease Severity but Do Not Protect against Typhoid Fever in a Controlled Human Infection Model

Abstract: Effective vaccines against Salmonella Typhi, a major cause of febrile illness in tropical regions, can have a significant effect as a disease control measure. Earlier work has shown that immunization with either of two Salmonella Typhi vaccines, licensed Ty21a or candidate M01ZH09, did not provide full immunity in a controlled human infection model. Here, we describe the human humoral immune responses to these oral vaccines and their functional role in protection after challenge with S. Typhi. Serum, obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Some studies suggest that anti-Vi IgG contributed to reduce disease symptoms and prevention of infection in some individuals [34] , [35] . However, recently, it was shown that bactericidal antibody reduced typhoid severity but not protection against disease in a human challenge model [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that anti-Vi IgG contributed to reduce disease symptoms and prevention of infection in some individuals [34] , [35] . However, recently, it was shown that bactericidal antibody reduced typhoid severity but not protection against disease in a human challenge model [36] .…”
Section: Discussionmentioning
confidence: 99%
“…This would indicate that opsono-phagocytosis is likely to be the prevailing antimicrobial mechanism mediated by anti-Salmonella antibodies. Furthermore, no correlation was found between protection afforded by live vaccination and SBA in a controlled human typhoid challenge model (111).…”
Section: Which Is the Main Protective Mechanism Of Anti-salmonella Anmentioning
confidence: 96%
“…Bactericidal activity is induced by vaccination, important for controlling the infection, leading to fewer symptoms, but not preventing infection [35]. A model has also been developed to look at Salmonella paratyphi A infection and, furthermore, in a heterologous re-challenge study: individuals with previous S. typhi exposure were not protected against rechallenge with S. paratyphi, but did show reduced overall attack rates, and a delayed time to diagnosis.…”
Section: Human Challenge Trials To Support Licensurementioning
confidence: 99%